(untitled) (Dissertare, 2021)
This article aims to analyze the functions of the human talent management area in a set of Venezuelan organizations, from the perspective of their managers. In order to help characterize the reality of managerial praxis in this area of ​​management, with emphasis on the role played by this area in the strategic approach of the organization. From a methodological point of view, the research has a quantitative approach, with a descriptive level and field design, and it covered a geographic space made up of eight states of the Bolivarian Republic of Venezuela, in which a sample of 38 managers was analyzed. It was possible to show the predominance of functions of an operational nature, largely leaving aside functions of a strategic nature. It is concluded that the human talent units are concentrated on traditional functions, so there are still challenges in recognizing the value that this unit can add in achieving the organization’s strategies and objectives. It was recommended to give greater space to the HR area in decision-making processes and in strategic management, as well as greater participation in efforts to build well-being in favor of employees, creating links of identification and loyalty towards the organization. Keywords: HR functions; human management; management of human talent in Venezuela, functions of human talent management.